Combination of silicon phase masks with time-domain spectroscopy for single-scan terahertz imaging - Jolly, A.; Gokhan, Fikri Serdar; Jolly, Jean-Claude; Hocquet, Steve; Chassagne, Bruno (SPRINGER HEIDELBERG, 2015)
We demonstrate the effectiveness of silicon phase masks to implement spatially resolved, multispectral imaging capabilities in the range of terahertz frequencies, using a standard setup of basic interest for time-domain spectrometry with a single-cell source and a single-cell detector. Our principle primarily aims at the development of robust and inexpensive systems. It consists of appropriate space-to-time encoding, in order to ensure single-scan triggering and then take advantage of rapid and self-consistent measurements in the two-dimensional space. The process enables very efficient discrimination giving access to a relevant spatial resolution in the analysis of small size, planar assemblies made of inhomogeneous materials. Benchmark results are provided to validate the concept, thanks to prototyping phase masks with 2 x 2 pixels, prior evidencing actual performance limitations in the case of 3 x 3 pixels. Due to the frequency bandwidth of 0.1-1.5 THz in our setup and to the available operating conditions, currently acceptable pixel resolutions lie in the range of 3-4 mm. Numerical modeling by means of finite elements helps to discuss these numbers and to investigate the relevant theoretical issues, figuring the main propagation issues in connection with a sub-picosecond seed pulse throughout various masks. This involves diffraction and trailing edge effects when crossing the mask together with residual, parasitic reflections. Finally, we give a consistent prospective for improved performance, via realistic updates regarding the architecture of the setup and complementary post-processing. Further values for the attainable spatial resolution then range from 5 x 5 to 6 x 6 pixels.
Keywords: PULSES